Incidence and predictors of new onset left ventricular diastolic dysfunction in asymptomatic patients with rheumatoid arthritis without overt cardiac disease: Diastolic dysfunction in rheumatoid arthritis - dal Piaz, Elena Costanza; Cioffi, Giovanni; Ognibeni, Federica; Dalbeni, Andrea; Giollo, Alessandro; Orsolini, Giovanni; Gatti, Davide; Idolazzi, Luca; Stefenelli, Carlo; Rossini, Maurizio; Viapiana, Ombretta (Monaldi Archives for Chest Disease, 2019)
Rheumatoid arthritis (RA) is associated with higher risk of heart failure. Several studies report that left ventricular (LV) diastolic dysfunction (LVDD), a silent precursor of heart failure, is widely present in RA patients. Very little is known about the factors related to the development of LVDD in this disease. In this study we assessed the incidence and the predictors of new-onset LVDD in RA patients. Two-hundred-ninety-five adults with RA without overt cardiac disease were prospectively analyzed from March 2014 to March 2015 by Doppler echocardiography. Among the 295 subjects evaluated, 217 (73.6%) had normal LV diastolic function and represented the final study population. At 1-year follow-up, 53 of 217 patients (24%) developed LVDD, which was of degree I (mild dysfunction) in all of them. By multivariate logistic regression analysis, lower E/A ratio of transmitral flow (ratio between the peak velocity of early diastolic â€œEâ€ wave and late diastolic â€œAâ€ wave of transmitral flow) was independently associated with new-onset LVDD [OR 0.17 (CI 0.09-0.57)], together with older age and higher systolic blood pressure. In a clinical predictive model derived from multivariate analysis, the new-onset LVDD rate event ranged from 0% (patients without any factor) to 75% (patients in whom the three predictors coexisted). A significant portion of patients with RA without overt cardiac disease develop LVDD at 1-year follow-up. This condition can be predicted by a simple clinical model which could improve the clinical management and the prognostic stratification of patients with RA.